Eroding knowledge: an ethnobotanical inventory in Eastern Amazonia's logging frontier - Shanley, P.; Rosa, N.A. (2004)
Responding to the decline of game, fruit and fiber, post-logging, communities along the Capim River in Pará, Brazil, requested that research be initiated into the value of non-timber forest products. As a first step, an ethnobotanical inventory of one hectare of mature terra firme forest was conducted. The percentage use-values described reflect that Capimenses know and use many species (60% of inventoried species). Differences between use-values reported in other South American inventories include: a higher degree of trade in timber; a lack of trade in non-timber products; the decreasing use of plants for technological purposes and the description of the use of many species in the past tense. During the longitudinal study, the 15 most highly valued fruit, nut, game attracting and medicinal species became included in the suite of species extracted by the timber industry.